Representasi Gangguan Mental Depresi dalam Drama Korea Daily Dose of Sunshine - Wulansari, Ratna; Urfan, Noveri Faikar (Unitri Press, 2024)
This research aims to determine the representation of depressive mental disorders, which is based on the increasing number of cases of depression in society, especially teenagers. This research uses the Korean drama Daily Dose of Sunshine as a research object to determine the representation of depressive mental disorders in the drama. The mental health issue that is raised as a drama aims to provide information and education to the public so that they care more about mental health, and can increase public awareness about the importance of mental health without thinking that it can give a bad stigma. This research method uses qualitative research with semantic analysis according to John Fiske's theory. The data collection technique in this research is by watching, observing and recording each scene in the episode which is analyzed based on the research objectives, then the data will be identified by formulating the problem. The data that has been grouped and identified will be examined using John Fiske's theory by grouping data at the Reality Level, Representation Level and Ideology Level. The results of this study show that depressive mental disorders are depicted in various scenes showing dissatisfaction, feelings of hopelessness, excessive sadness, feelings of satisfaction and even rejection or bad actions from society. Mental disorders are sensitive conditions that are still underestimated and underestimated by society, especially in Indonesia. Abstrak Penelitian ini bertujuan untuk mengetahui representasi gangguan mental depresi, didasarkan pada peningkatan jumlah kasus depresi di masyarakat terutama remaja. Penelitian ini menggunakan drama korea Daily Dose of Sunshine sebagai objek penelitian untuk mengetahui representasi gangguan mental depresi dalam drama tersebut. Isu kesehatan mental yang diangkat menjadi drama bertujuan untuk memberikan informasi dan edukasi kepada masyarakat agar lebih peduli terhadap kesehatan mental, serta dapat meningkatkan kesadaran publik tentang pentingnya kesehatan mental tanpa berfikir akan mendapat stigma buruk di masyarakat. Metode penelitian ini menggunakan penelitian kualitatif dengan analisis semotika menurut teori John Fiske. Teknik pengumpulan data dalam penelitian ini adalah dengan menonton, mengamati, dan mencatat setiap adegan dalam episode yang dianalisis berdasarkan tujuan penelitian, kemudian data di identifikasi dengan rumusan masalah. Data yang telah dikelompokan, diteliti menggunakan teori John Fiske dengan mengelompokkan data pada Level Realitas, Level Representasi, dan Level Ideologi. Hasil penelitian ini memperlihatkan bahwa gangguan mental depresi digambarkan dalam berbagai adegan yang menunjukan penolakan, rasa keputusasaan, kesedihan yang berlebihan, merasa bersalah hingga penolakan atau perlakukan buruk dari masyarakat. Gangguan mental merupakan kondisi yang sensitif yang masih disepelekan dan dipandang sebelah mata oleh masyarakat terlebih di Indonesia.